2014
DOI: 10.1161/circresaha.115.304437
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Hypoxia Potentiates Interleukin-1β Production in Activated Human Macrophages

Abstract: Rationale Inflammation drives atherogenesis. Animal and human studies have implicated interleukin (IL)-1β in this disease. Moderate hypoxia, a condition that prevails in the atherosclerotic plaque, may conspire with inflammation and contribute to the evolution and complications of atherosclerosis through mechanisms that remain incompletely understood. Objective This study investigated the links between hypoxia and inflammation by testing the hypothesis that moderate hypoxia modulates IL-1β production in acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 55 publications
2
97
0
2
Order By: Relevance
“…This study demonstrated that hypoxia could augment NLRP3 gene expression and protein levels in both LPS-treated and untreated human macrophages in vitro, and promoted pro-IL-1 production by limiting its autophagic degradation [20] .…”
Section: Hypoxia Priming Of the Nlrp3 Inflammasomementioning
confidence: 67%
See 1 more Smart Citation
“…This study demonstrated that hypoxia could augment NLRP3 gene expression and protein levels in both LPS-treated and untreated human macrophages in vitro, and promoted pro-IL-1 production by limiting its autophagic degradation [20] .…”
Section: Hypoxia Priming Of the Nlrp3 Inflammasomementioning
confidence: 67%
“…Hypoxia is known to promote pro-IL-1 production and has been implicated in the pathogenesis of several diseases including atherogenesis, where patient samples display increased NLRP3-derived IL-1 production [20] . This study demonstrated that hypoxia could augment NLRP3 gene expression and protein levels in both LPS-treated and untreated human macrophages in vitro, and promoted pro-IL-1 production by limiting its autophagic degradation [20] .…”
Section: Hypoxia Priming Of the Nlrp3 Inflammasomementioning
confidence: 99%
“…Local production of M-CSF promotes the survival of foam cells and contributes to development of the early-stage, but not late-stage, atherosclerotic lesions (20,21 F-FDG PET studies (8)(9)(10)(11)(12)(13)(14). For example, glucose uptake and glycolysis are induced by bacterial-derived products, such as lipopolysaccharide (13), modified low-density lipoprotein (15,16), or hypoxia (17). However, the link between a proinflammatory macrophage phenotype and enhanced glucose uptake may be valid for only a number of stimuli and does not represent a universal phenomenon (9,14).…”
Section: Experimental Studies: Regulation Of Macrophage Glucose Metabmentioning
confidence: 99%
“…Of note, recent data have suggested that ischemic stress, such as moderate hypoxia, could potentiate inflammatory response in human primary macrophages. 34 Therefore, further analysis of different atherogenic stimuli in different cell types will be needed to better describe the pathways involved in the regulation of ATG16L1 expression.…”
Section: Discussionmentioning
confidence: 99%